Volume 4: Heat Transfer; Electric Power; Industrial and Cogeneration 1989
DOI: 10.1115/89-gt-187
|View full text |Cite
|
Sign up to set email alerts
|

An Experimental Study of Heat Transfer and Film Cooling on Low Aspect Ratio Turbine Nozzles

Abstract: The effects of the three-dimensional flow field on the heat transfer and the film cooling on the endwall, suction and pressure surface of an airfoil were studied using a low speed, fully annular, low aspect h/c=0.5 vane cascade. The predominant effects that the horseshoe vortex, secondary flow, and nozzle wake increases in the heat transfer and decreases in the film cooling on the suction vane surface and the endwall were clearly demonstrated. In addition, it was demonstrated that secondary flow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

1992
1992
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 10 publications
2
19
0
Order By: Relevance
“…He found that both heat transfer and film-cooling on the endwall are influenced by secondary flow. A similar observation was made by Takeishi et al (1989). Their leading edge horseshoe vortex, Endwall Static Pressure Contours Without Coolant Ejection (Harrison (1989)) Expressed as (11_, -p)/(11, -p az,)…”
Section: Introductionsupporting
confidence: 69%
“…He found that both heat transfer and film-cooling on the endwall are influenced by secondary flow. A similar observation was made by Takeishi et al (1989). Their leading edge horseshoe vortex, Endwall Static Pressure Contours Without Coolant Ejection (Harrison (1989)) Expressed as (11_, -p)/(11, -p az,)…”
Section: Introductionsupporting
confidence: 69%
“…Considering the complex flowfield in the rotating rig test, including the vane wakes, a reasonable comparison is very difficult. Film cooling with a rotating rig was experimentally investigated by Dring et al, 48 Abhari and Epstein, 49 and Takeishi et al 50 ; in each case, comparisons to stationary blade configurations were attempted.…”
Section: G Rotating Rig Testsmentioning
confidence: 99%
“…Coolant ejection locations have to be viewed with respect to the three-dimensional separation lines on the endwall, taking account of the fact that these can be changed due to upstream endwall coolant ejection. Previous investigations of endwall filmcooling, such as the ones by Blair (1974), Takeishi et al (1989), Granser and Schulenberg (1990), Bourguignon (1985), Bario et al (1989), Harasgama and Burton (1991), Jabbari et al (1994), Goldman and McLallin (1977) and Sieverding and Wilputte (1980) support these conclusions.…”
Section: Introductionmentioning
confidence: 60%